Common fixed-point theorems for nonlinear weakly contractive mappings - Chandok, S.; Khan, M.S.; Abbas, M. (Український математичний журнал, 2014)
Some common fixed-point results for mappings satisfying a nonlinear weak contraction condition within the framework of ordered metric spaces are obtained. The accumulated results generalize and extend several comparable results well-known from the literature.